The Lon protease is essential for full virulence in Pseudomonas aeruginosa. - Elena B M Breidenstein; Laure Janot; Janine Strehmel; Lucia Fernandez; Patrick K Taylor; Irena Kukavica-Ibrulj; Shaan L Gellatly; Roger C Levesque; Joerg Overhage; Robert E W Hancock (PLoS ONE, 2012)
Pseudomonas aeruginosa PAO1 lon mutants are supersusceptible to ciprofloxacin, and exhibit a defect in cell division and in virulence-related properties, such as swarming, twitching and biofilm formation, despite the fact that the Lon protease is not a traditional regulator. Here we set out to investigate the influence of a lon mutation in a series of infection models. It was demonstrated that the lon mutant had a defect in cytotoxicity towards epithelial cells, was less virulent in an amoeba model as well as a mouse acute lung infection model, and impacted on in vivo survival in a rat model of chronic infection. Using qRT-PCR it was demonstrated that the lon mutation led to a down-regulation of Type III secretion genes. The Lon protease also influenced motility and biofilm formation in a mucin-rich environment. Thus alterations in several virulence-related processes in vitro in a lon mutant were reflected by defective virulence in vivo.